UnetTransCNN: integrating transformers with convolutional neural networks for enhanced medical image segmentation - Xie, Yi-Hang; Huang, Bo-Song; Li, Fan (Frontiers in Oncology, 2025)
IntroductionAccurate segmentation of 3D medical images is crucial for clinical diagnosis and treatment planning. Traditional CNN-based methods effectively capture local features but struggle with modeling global contextual dependencies. Recently, transformer-based models have shown promise in capturing long-range information; however, their integration with CNNs remains suboptimal in many hybrid approaches.MethodsWe propose UnetTransCNN, a novel parallel architecture that combines the strengths of Vision Transformers (ViT) and Convolutional Neural Networks (CNNs). The model features an Adaptive Fourier Neural Operator (AFNO)-based transformer encoder for global feature extraction and a CNN decoder for local detail restoration. Multi-scale skip connections and adaptive global-local coupling units are incorporated to facilitate effective feature fusion across resolutions. Experiments were conducted on the BTCV and MSD public datasets for multi-organ and tumor segmentation.ResultsUnetTransCNN achieves state-of-the-art performance with an average Dice score of 85.3%, outperforming existing CNN- and transformer-based models on both large and small organ structures. The model notably improves segmentation accuracy for challenging regions, achieving Dice score gains of 6.382% and 6.772% for the gallbladder and adrenal glands, respectively. Robustness was demonstrated across various hyperparameter settings and imaging modalities.DiscussionThese results demonstrate that UnetTransCNN effectively balances local precision and global context, yielding superior segmentation performance in complex anatomical scenarios. Its parallel design and frequency-aware encoding contribute to enhanced generalizability, making it a promising tool for high-precision medical image analysis.